Outcomes of free flap reconstructions with near‐infrared spectroscopy (NIRS) monitoring: A systematic review. Issue 2 (30th October 2019) - Newton, Ethan; Butskiy, Oleksandr; Shadgan, Babak; Prisman, Eitan; Anderson, Donald W.
Abstract: Background: Free flap failure or vascular compromise remains a dreadful complication of microvascular free tissue transfer. Near‐infrared spectroscopy (NIRS) is a novel technique for free flap monitoring that has the propensity for early detection of vascular compromise when compared to the current gold standard, clinical monitoring (CM). The objective of this review is to evaluate the efficacy of a NIRS system in the postoperative monitoring of free flaps and its effect on flap salvage. Methods: A comprehensive literature review was performed including English‐language articles evaluating the use of NIRS in free flap monitoring. MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), OVID, and Web of Science were searched upto December 2017. Results: A total of 590 articles were identified, and 10 articles were included for analysis. Overall, flaps with vascular compromise monitored with NIRS had a significantly higher salvage rate of 89% compared with a salvage rate of 50% in the flaps monitored by CM alone ( p  < .01). Partial loss occurred in 15% of the successful salvages in the NIRS group versus 80% with CM alone ( p  < .01). Detection of vascular compromise by NIRS preceded clinical signs on average by 82 ± 49 min. NIRS was accurate in detecting compromised flaps with a low false‐positive and false‐negative rate. Conclusion: Despite lack of robust data, NIRS has the potential to be an objective, accurate, and continuous postoperative free flap monitoring technique with a greater flap salvage rate than CM alone.